Growth and development of salinity-exposed rice (“Oryza sativa”) rhizo-inoculated with “Bacillus subtilis” under different pH levels - Francis Aibuedefe IGIEBOR; Beckley IKHAJIAGBE; Geoffrey Obinna ANOLIEFO (Studia Universitatis Babeș-Bolyai. Biologia)
The study investigated the effects of varying pH levels on the growth and development of salt-exposed rice (Oryza sativa L.) after inoculation with Bacillus subtilis. Germinated rice seedlings (var. FARO 44) were sown in garden soils amended to 100 mM NaCl, and were thereafter inoculated with Bacillus subtilis. The transplants were subsequently exposed to periodic wetting with 5 mL of pH-buffered water (pH 3, 5, 7, 9 and 11) every day, and with 5 mL of 100 mM NaCl every 4 days. The set up was monitored during a 30-day period. Results showed significant reduction in chlorophyll a and b as well as lycopene and tocopherol contents of leaves due to changes in the lipid-to-protein ratio of pigment-protein complex or increased chlorophyllase activity and drought stress. There were improved morphological characteristics such as plant height, sheath and foliar dimensions due to inoculation of B. subtilis. Increase in salinity resulted in a decrease in plant height, leaf length and sheath. Inoculation not only promoted rice growth, but also enhanced rice tolerance towards salinity owing to the fact that FARO 44 is a salinity-tolerant rice variety. A better understanding of the interaction between microbial inoculants and soil conditions is required to harness the desired benefits towards improving crop development.